Low-density microcellular foaming ceramic based on waste refractory material and manufacturing method thereof

By combining the passivation-treated aluminum-silicon and carbon-like waste refractory materials with feldspar solid waste materials, the performance problems of waste refractory materials in the preparation of recycled materials and the high cost of traditional foaming agents is solved, and the The preparation of high-performance low-density microporous foamed ceramics promotes the greening of ceramics and environmental protection.

CN119161198APending Publication Date: 2024-12-20JINGDEZHEN KITO CERAMIC CO LTD +3
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411306879.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize waste refractory materials, resulting in poor body forming performance and sintering performance in the preparation of recycled materials. In addition, the high-temperature foaming agents are used in the preparation of traditional foamed ceramics, making it difficult to achieve low-density microporous foaming. Preparation of ceramics.

Method used

Using low-density microporous foamed ceramics based on waste refractory materials, the high melting point crystal phase of these materials at high temperature is mixed by passing the aluminum silicon and carbon waste refractory materials and mixed with feldspar solid waste materials after passing the passivation treatment. Oxidation and decomposition characteristics reduce bubble convergence and form a uniform low-density microporous structure.

Benefits of technology

Low-density microporous foamed ceramics with high porosity, small average pore size, high porosity and moderate compressive strength are achieved, which reduces the cost of using foaming agents and promotes the greening of ceramics and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161198A_ABST
    Figure CN119161198A_ABST
Patent Text Reader

Abstract

The invention discloses a low-density microcellular foamed ceramic based on waste refractory materials and a manufacturing method thereof, and belongs to the technical field of porous ceramic material preparation, a blank comprises the following components: 0.1-1 part of a carbonaceous waste refractory material, 20-40 parts of a feldspar solid waste material, 0.1-0.2 part of a dispersant and 1-6 parts of a passivated aluminum-silicon waste refractory material. After being passivated, the aluminum-silicon waste refractory material is doped into the foamed ceramic, and the high-temperature-resistant crystal phase composition of the aluminum-silicon waste refractory material can stably exist in a molten green body, so that the stability of pores in the foaming stage is promoted; the low-temperature degradation impurities of the carbon waste refractory material are few, and the carbon waste refractory material can be oxidized and decomposed to generate gas after being concentrated at high-temperature heat preservation, so that uniform closed pores can be formed; the main raw materials used in the invention are industrial solid wastes and waste refractory materials, which not only contributes to green development of foamed ceramics, but also contributes to environmental protection and sustainable development of solid waste enterprises.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-density microporous foamed ceramic based on waste refractory materials and a preparation method thereof, belonging to the technical field of porous ceramic material preparation. Background Art

[0002] With the development of my country's metallurgical and other thermal industries, the demand for refractory materials has also increased significantly. As a major producer and seller of refractory materials, my country's total output of refractory materials reached 23.01 million tons in 2022. The consumption of refractory materials in use also produces a large amount of waste refractory materials. At present, most of these waste refractory materials are landfilled and difficult to use effectively. Studies have shown that waste refractory materials contain a large amount of high-temperature crystalline phases. After impurities are removed and crushed, they can be reused as recycled materials in the preparation of refractory materials. However, the internal grain structure of the fired refractory material is stable, and the plasticity and sinterability are poor, which leads to the reduction of the green body forming performance and sintering performance when it is used as recycled material to prepare refractory materials.

[0003] Foamed ceramics are made of clay, mine tailings, and industrial solid waste as the main raw materials, and are mixed with auxiliary raw materials such as flux, foam stabilizer, and high-temperature foaming agent. After uniform mixing, they are sintered and foamed at high temperature. It is a new type of lightweight thermal insulation building material. The interior of the foamed ceramic is full of dense closed pores, which makes it lightweight, high-strength, waterproof and moisture-proof, mildew-proof and antibacterial, acid and alkali-resistant, freeze-thaw-resistant, thermal insulation, sound insulation and noise reduction. It can be widely used in building wall insulation, fire isolation belts, building self-insulation and other fields. Porosity and pore structure are the main factors affecting the performance of foamed ceramics. Foamed ceramics with high porosity usually have good thermal insulation properties, but their strength is low. On the contrary, foamed ceramics with low porosity have higher strength, but insufficient thermal insulation performance. In addition, at the same porosity, the smaller the pore size, the more concentrated the pore size distribution, the higher the integrity of the pore wall, and the better the performance of the foamed ceramic. Therefore, how to prepare microporous foamed ceramics with excellent pore structure is the key to making high-performance foamed ceramics.

[0004] The preparation principle of foamed ceramics is to introduce an appropriate amount of high-temperature foaming agent into the blank. The foaming agent undergoes a chemical reaction at high temperature to generate a large amount of volatile gas. At this time, the blank in a viscous flow state wraps the gas, causing the material to expand as a whole, forming dense closed pores inside, and finally obtaining a porous, lightweight material structure. However, the bubbles are in a thermodynamically unstable state. During the growth of the bubbles, due to the effects of surface tension and buoyancy, the bubbles are very easy to float, coalesce, and burst, forming large pores and interconnected pores, which will be detrimental to improving the performance of foamed ceramics. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the present invention provides a low-density microporous foamed ceramic based on waste refractory materials and a preparation method thereof. During the foaming process, bubbles are not easy to coalesce, and low-density microporous foamed ceramics can be produced at low cost.

[0006] The technical solution adopted by the present invention to solve its technical problem is: In the first aspect, the present application provides a low-density microporous foamed ceramic based on waste refractory materials. The composition of the blank includes, by mass, 0.1 to 1 part of carbonaceous waste refractory materials, 20 to 40 parts of feldspar solid waste materials, 0.1 to 0.2 parts of dispersant and 1 to 6 parts of passivated aluminum-silicon waste refractory materials.

[0007] The low-density microporous foamed ceramics based on waste refractory materials provided by the present application use waste refractory materials as raw materials. These waste refractory materials have been calcined at high temperatures, have high crystal phase stability, and have few low-temperature degradation impurities. Specifically, aluminosilicate waste refractory materials contain a large number of high-melting point crystal phases, which can be made into micropowders composed of high-melting point grains by grinding. During the firing process of foamed ceramics, these high-melting point grains can be suspended in the silicate melt, increasing the liquid phase viscosity, improving the stability of the liquid film, and reducing the aggregation of bubbles; while carbonaceous waste refractory materials have few low-temperature degradation impurities. During the firing process, the time for bubble formation is delayed, reducing the chance of bubble aggregation, and the time for bubble generation is more concentrated, which is conducive to the formation of uniform closed pores.

[0008] Furthermore, the low-density microporous foamed ceramic based on waste refractory materials has a porosity of 88% to 95%, an average pore size of ≤1 mm, a closed porosity of ≥96%, a compressive strength of 0.2 MPa to 6 MPa, and a thermal conductivity of 0.05 W / (m·k) to 0.092 W / (m·k).

[0009] Furthermore, the aluminosilicate waste refractory material includes any one of a corundum refractory material, a cordierite refractory material, a spinel refractory material, and an olivine refractory material.

[0010] Furthermore, the carbonaceous waste refractory material comes from at least one of carbon bricks, graphite bricks, and silicon carbide carbon products, and the refractory temperature is ≥1300°C.

[0011] Furthermore, the feldspar solid waste material includes at least one of feldspar tailings, copper tailings, lithium tailings, and gold tailings, wherein the content of feldspar minerals is ≥40%, and the chemical composition satisfies: 15%≤Al2O3≤25%, 50%≤SiO2≤80%, Na2O+K2O≥5%, and 2%≤CaO+MgO≤10%.

[0012] Furthermore, the particle size of the blank satisfies: the particle size range of the aluminosilicate waste refractory material is 1 μm to 10 μm, the particle size of the carbonaceous waste refractory material is ≤10 μm, and the particle size of the feldspar solid waste material is ≤45 μm.

[0013] Furthermore, the dispersant includes at least one of triethanolamine, cyclohexane acid soap, polysiloxane, tricarboxylic acid ethylamine, sodium polyacrylate, and sodium hexametaphosphate.

[0014] In a second aspect, the present application provides a method for producing a low-density microporous foamed ceramic based on waste refractory materials, comprising the following steps: Aluminosilicate waste refractory materials, carbonaceous waste refractory materials and feldspar solid waste materials are respectively subjected to impurity removal, drying, crushing and grinding to form micro powders, and then sieved to obtain fine powders; placing the fine powder obtained from the aluminum-silicon waste refractory material in a high-temperature furnace for passivation treatment and then cooling; 1 to 6 parts by mass of the passivated fine powder made from the aluminum-silicon waste refractory material, 0.1 to 1 part of the fine powder made from the carbonaceous waste refractory material, 20 to 40 parts of the fine powder made from the feldspar solid waste material, and 0.1 to 0.2 parts of the dispersant are placed in a forced mixer and dry mixed for 180 minutes to 480 minutes to form a blank; The blank is piled in a refractory sagger or pressed into shape by a press, and then placed in a high-temperature furnace, heated to 1150° C. to 1250° C., kept warm for 30 min to 90 min, fired and foamed, to obtain a low-density microporous foamed ceramic based on waste refractory materials.

[0015] Aluminosilicate waste refractory materials contain a large amount of high-melting-point crystal phases, which can be ground into micropowders composed of high-melting-point grains. During the firing process of foamed ceramics, these high-melting-point grains can be suspended in the silicate melt, increasing the liquid phase viscosity, improving the stability of the liquid film, and reducing the aggregation of bubbles, thereby realizing the preparation of microporous foamed ceramics. On the other hand, carbon-containing refractory materials can be oxidized and decomposed to produce gas, so they can be used as high-temperature foaming agents for foamed ceramics. Compared with traditional foaming agents, these refractory waste materials have been calcined at high temperatures, have high crystal phase stability, and are not easy to decompose at low temperatures, so they have higher foaming efficiency.

[0016] Furthermore, the passivation process is: heating to 500°C~900°C at 5°C / min~12°C / min, keeping warm for 10min~60min, then cooling to 400°C~800°C at -2°C / min, keeping warm for 30min~180min, and finally cooling to room temperature with the furnace. High temperature passivation can solve the problem of disordered atomic arrangement on the surface of crushed refractory powder particles.

[0017] Furthermore, the forced mixer is a rapid powder mixer with an eccentric stirring blade, and the rotation speed of the eccentric stirring blade is 50 r / min ~ 200 r / min.

[0018] The beneficial effects of the present invention are as follows: the present invention processes aluminum-silicon waste refractory materials into microparticles, which are passivated and then added to foamed ceramics. The high-temperature resistant crystal phase composition can stably exist in the molten green body, promoting the stability of pores in the foaming stage; and the carbonaceous waste refractory materials have few impurities due to low-temperature degradation, and will only be oxidized and decomposed to produce gas when kept warm at high temperature, thus forming uniform closed pores; the main raw materials used in the present invention are industrial solid waste and waste refractory materials, which not only contributes to the green development of foamed ceramics, but also contributes to environmental protection and the sustainable development of solid waste enterprises.

[0019] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or understood by practicing the present application. The purpose and other advantages of the present application can be realized and obtained by the structures particularly pointed out in the written description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is an electron microscope image of a low-density microporous foamed ceramic based on waste refractory materials provided in Example 1 of the present application. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution of the embodiments of the present disclosure is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] It should be understood that, under the premise of no conflict, any and all embodiments of the present invention can be combined with the technical features in any other embodiment or multiple other embodiments to obtain another embodiment. The present invention includes such a combination to obtain another embodiment.

[0023] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter belongs. If there are multiple definitions for a term, the definition herein shall prevail.

[0024] Standing air has a very high thermal resistance, so porous ceramics used for filtration pursue low closed porosity. On the contrary, porous ceramics used for thermal insulation should pursue as high a closed porosity as possible. Moreover, for porous ceramics used for thermal insulation, the pores should be as numerous as possible and the pore size should be as small as possible to reduce convective heat transfer and reduce heat conduction (more pores will cause the solid part in the porous ceramic to be thinner and more tortuous, which is equivalent to a longer heat conduction path). In the prior art, foamed ceramics are mostly prepared with raw materials containing low-melting-point aluminum-silica minerals (including industrial solid waste). The melt viscosity produced during the foaming stage is low, which causes bubbles to coalesce and the pore size to become larger. Therefore, increasing the viscosity of the high-temperature melt of the foamed ceramic and increasing the strength of the liquid film after the bubble is formed are the key to preparing microporous foamed ceramics. In addition, high-temperature foaming agents are key components for preparing foamed ceramics. Currently, foamed ceramics mainly use high-temperature foaming agents such as SiC micropowder, graphite powder, and Fe2O3. For example, patent CN116082059A discloses a method for producing low-density foamed ceramics using all solid waste as raw materials. Although this method uses a large amount of industrial solid waste such as riverbed mud, steel slag, and coal gangue as raw materials, which effectively reduces the preparation cost of foamed ceramics, it still needs to add a small amount of SiC micropowder as a foaming agent. Therefore, how to effectively reduce the cost of using the foaming agent is an important issue that needs to be solved in the current large-scale production of foamed ceramics.

[0025] In response to the above problems, an embodiment of the present application provides a low-density microporous foamed ceramic based on waste refractory materials. Calculated by mass, the composition of the blank includes 0.1 to 1 part of carbonaceous waste refractory materials, 20 to 40 parts of feldspar solid waste materials, 0.1 to 0.2 parts of dispersant and 1 to 6 parts of passivated aluminum-silicon waste refractory materials.

[0026] The obtained low-density microporous foamed ceramic has a porosity of 88%~95%, an average pore size of ≤1mm, a closed porosity of ≥96%, a compressive strength of 0.2 MPa~6MPa, and a thermal conductivity of 0.05 W / (m·k)~0.092W / (m·k).

[0027] The embodiments of the present application utilize a variety of waste refractory materials and feldspar solid waste materials to prepare foamed ceramics without the need to add additional high-purity foaming agents and foam stabilizers, which not only saves the preparation cost of the foamed ceramics, but also enables the preparation of low-density microporous foamed ceramics.

[0028] Accordingly, the embodiment of the present application provides a method for producing low-density microporous foamed ceramics based on waste refractory materials, comprising the following steps: S1: remove impurities, dry, crush and grind aluminosilicate waste refractory materials, carbonaceous waste refractory materials and feldspar solid waste materials into micro powder, and then sieve to obtain fine powder.

[0029] S2: placing the fine powder made from the aluminum silicon waste refractory material in a high temperature furnace for passivation treatment and then cooling.

[0030] S3: By mass, 1 to 6 parts of passivated fine powder made from aluminum-silicon waste refractory materials, 0.1 to 1 part of fine powder made from carbonaceous waste refractory materials, 20 to 40 parts of fine powder made from feldspar solid waste materials, and 0.1 to 0.2 parts of dispersant are placed in a forced mixer and dry mixed for 180 minutes to 480 minutes to form a blank.

[0031] S4: The blanks are piled in a refractory sagger or pressed into shape by a press, and then placed in a high-temperature furnace, heated to 1150°C~1250°C, and kept warm for 30min~90min to sinter and foam, thereby obtaining a low-density microporous foamed ceramic based on waste refractory materials.

[0032] This not only provides a new method for the preparation of lightweight foamed ceramics, but also makes resourceful use of waste refractory materials. The process is simple and has significant economic and social benefits.

[0033] If a regular thermal insulation material is to be obtained, after step S4, the surface can be cut after cooling to room temperature to obtain a regular microporous foamed ceramic product.

[0034] Specifically, the blank needs to meet the following requirements: the particle size range of aluminum-silica waste refractory materials is 1μm~10μm, the particle size of carbonaceous waste refractory materials is ≤10μm, and the particle size of feldspar solid waste is ≤45μm. Alumina-silica waste refractory waste contains a large amount of high-melting point crystal phases. Grinding to 1μm~10μm can increase the uniformity of these high-melting point crystals suspended in the silicate melt during the firing process, which is more conducive to increasing the liquid phase viscosity, improving the stability of the liquid film, reducing the aggregation of bubbles, and facilitating the preparation of microporous foamed ceramics.

[0035] Aluminosilicate waste refractory materials include any one of corundum refractory materials, cordierite refractory materials, spinel refractory materials, and olivine refractory materials; preferably, the product form of aluminosilicate waste refractory materials includes but is not limited to any one of refractory bricks and refractory castables. However, after the aluminosilicate waste refractory materials are crushed into fine powder, they are not passivated at high temperature, which will cause them to be easily melted at high temperature and have poor foam stabilization effect.

[0036] The passivation treatment process in the embodiment of the present application is: heating to 500°C~900°C at 5°C / min~12°C / min, keeping warm for 10min~60min, then cooling to 400°C~800°C at -2°C / min, keeping warm for 30min~180min, and finally cooling to room temperature with the furnace.

[0037] The carbonaceous waste refractory material comes from at least one of carbon bricks, graphite bricks and silicon carbide carbon products, and the refractory temperature is ≥1300°C.

[0038] Compared with general foaming agents, carbonaceous waste refractory materials that have been in service at high temperatures have fewer impurities when degraded at low temperatures; this is equivalent to the fact that for carbonaceous waste refractory materials that have been in service at high temperatures, the temperature range in which ordinary carbonaceous materials produce gas is expanded to the low temperature section. Carbon bricks that have been in service have carbon inside that is mostly in the form of graphite, and have a higher decomposition temperature. Similarly, SiC refractory materials that have been in service at high temperatures have different SiC grain sizes. These will have an impact on the production of foamed ceramics. Carbonaceous waste refractory materials can be used as high-temperature foaming agents for foamed ceramics by utilizing the characteristics of being oxidatively decomposed and producing gas. Compared with traditional foaming agents, these refractory waste materials have been in service at high temperatures, have high crystal phase stability, and are not easy to decompose at low temperatures, so they have higher foaming efficiency.

[0039] Preferably, before step S3, the fine powder prepared from the carbonaceous waste refractory material is also subjected to a high-temperature passivation treatment with the same temperature requirements as above, which can be carried out under a protective atmosphere, and can further narrow the temperature range of decomposition of the carbonaceous waste refractory material, making it more concentrated to produce gas at high temperature.

[0040] Feldspar solid waste materials include at least one of feldspar tailings, copper tailings, lithium tailings, and gold tailings, wherein the content of feldspar minerals is ≥40%, and the chemical composition satisfies: 15%≤Al2O3≤25%, 50%≤SiO2≤80%, Na2O+K2O≥5%, 2%≤CaO+MgO≤10%. Among them, by limiting the potassium and sodium content in feldspar solid waste materials, only when the potassium and sodium content reaches a certain proportion, the refractory waste that can be added to the formula will also increase, and the above formula is more conducive to reducing production costs.

[0041] In step S4, if a press is used for pressing and forming, the pressing and forming pressure may be 10 MPa; if the blanks are piled in a refractory sagger, they may be piled loosely.

[0042] Example 1 (1) Remove impurities from spinel refractory brick waste, carbon brick waste, and lithium tailings, dry, crush, grind into micro powder, and then sieve into fine powder for standby use. After sieving, all the spinel refractory brick waste powder passes through a 10μm square hole sieve, and particles below 1μm are sieved out; all the carbon brick waste powder passes through a 10μm square hole sieve; and all the lithium tailings powder passes through a 45μm square hole sieve.

[0043] (2) The obtained spinel refractory brick waste powder is placed in a high-temperature furnace, heated to 800°C at 5°C / min, kept at this temperature for 30 minutes, then cooled to 400°C at -2°C / min, kept at this temperature for 30 minutes, and finally cooled to room temperature with the furnace for use.

[0044] (3) According to the weight ratio, 6 parts of spinel refractory brick waste powder, 0.15 parts of carbon brick waste powder, 40 parts of lithium tailings powder, 0.1 parts of triethanolamine and 0.1 parts of sodium polyacrylate dispersant were placed in a forced mixer and dry mixed at a speed of 100 r / min for 180 min to form a blank.

[0045] (4) The blanks are loosely piled in a refractory sagger, placed in a high-temperature furnace, heated to 1180°C at a rate of 4°C / min, and kept at that temperature for 60 min to sinter and foam.

[0046] (5) The foamed body is cooled to room temperature and the surface is cut to obtain a regular microporous foamed ceramic product.

[0047] The pore structure of the foamed ceramic product is as follows Figure 1 As shown, it can be seen that the size of each pore is relatively uniform and the pore diameter is small. The measured porosity of the material is 88.1%, the average pore diameter is 0.75mm, the closed porosity is 99.1%, the compressive strength is 5.91MPa, and the thermal conductivity is 0.092W / (m·k).

[0048] Example 2 (1) Remove impurities from spinel refractory brick waste, carbon brick waste, and feldspar tailings, dry, crush, grind into micro powder, and then sieve into fine powder for standby use. After sieving, all the spinel refractory brick waste powder passes through a 10μm square hole sieve, and particles below 1μm are sieved out; all the carbon brick waste powder passes through a 10μm square hole sieve; and all the feldspar tailings powder passes through a 45μm square hole sieve.

[0049] (2) The obtained spinel refractory brick waste powder is placed in a high-temperature furnace, heated to 800°C at 5°C / min, kept at this temperature for 30 minutes, then cooled to 400°C at -2°C / min, kept at this temperature for 30 minutes, and finally cooled to room temperature with the furnace for use.

[0050] (3) According to the mass proportions, 4 parts of spinel refractory brick waste powder, 0.5 parts of carbon brick waste powder, 40 parts of feldspar tailings powder, 0.1 parts of triethanolamine, and 0.05 parts of sodium hexametaphosphate dispersant were placed in a forced mixer and dry mixed at a speed of 50 r / min for 240 min to form a blank.

[0051] (4) The blanks are loosely piled in a refractory sagger, placed in a high-temperature furnace, heated to 1200°C at 4°C / min, and kept at that temperature for 60 min to sinter and foam.

[0052] (5) The foamed body is cooled to room temperature and the surface is cut to obtain a regular microporous foamed ceramic product.

[0053] The obtained foamed ceramic product has a porosity of 90.5%, an average pore diameter of 0.98 mm, a closed porosity of 98.4%, a compressive strength of 4.89 MPa, and a thermal conductivity of 0.085 W / (m·k).

[0054] Example 3 (1) Remove impurities from cordierite refractory brick waste, silicon carbide plate waste, and lithium tailings, dry, crush, grind into micro powder, and then sieve into fine powder for standby use. After sieving, all the cordierite refractory brick waste powder passes through a 10μm square hole sieve, and the particles below 1μm are sieved out; all the silicon carbide plate waste powder passes through a 10μm square hole sieve; and all the lithium tailings powder passes through a 45μm square hole sieve.

[0055] (2) The obtained cordierite refractory brick waste powder was placed in a high-temperature furnace, heated to 700°C at 6°C / min, kept at this temperature for 30 minutes, then cooled to 400°C at -2°C / min, kept at this temperature for 60 minutes, and finally cooled to room temperature with the furnace for use.

[0056] (3) According to the mass proportions, 6 parts of cordierite refractory brick waste powder, 0.1 parts of silicon carbide plate waste powder, 35 parts of lithium tailings powder, and 0.1 parts of triethanolamine were placed in a forced mixer and dry mixed at a speed of 100 r / min for 180 min to form a blank.

[0057] (4) The blanks are loosely piled in a refractory sagger, placed in a high-temperature furnace, heated to 1180°C, and kept warm for 90 minutes to sinter and foam.

[0058] (5) The foamed body is cooled to room temperature and the surface is cut to obtain a regular microporous foamed ceramic product.

[0059] The porosity of the foamed ceramic product is 88.5%, the average pore diameter is 0.84 mm, the closed porosity is 98.9%, the compressive strength is 5.12 MPa, and the thermal conductivity is 0.089 W / (m·k).

[0060] Example 4 (1) Remove impurities from cordierite refractory brick waste, silicon carbide plate waste, and feldspar tailings, dry, crush, grind into micro powder, and then sieve into fine powder for standby use. After sieving, all the cordierite refractory brick waste powder passes through a 10μm square hole sieve, and particles below 1μm are sieved out; all the silicon carbide plate waste powder passes through a 10μm square hole sieve; and all the feldspar tailings powder passes through a 45μm square hole sieve.

[0061] (2) The obtained cordierite refractory brick waste powder was placed in a high-temperature furnace, heated to 700°C at 6°C / min, kept at this temperature for 60 min, then cooled to 400°C at -2°C / min, kept at this temperature for 120 min, and finally cooled to room temperature with the furnace for use.

[0062] (3) According to the weight ratio, 6 parts of cordierite refractory brick waste powder, 0.1 parts of silicon carbide plate waste powder, 35 parts of feldspar tailings powder, and 0.1 parts of triethanolamine were placed in a forced mixer and dry mixed at a speed of 120 r / min for 180 min to form a blank.

[0063] (4) The blanks are loosely piled in a refractory sagger, placed in a high-temperature furnace, heated to 1220°C, and kept warm for 60 minutes to sinter and foam.

[0064] (5) The foamed body is cooled to room temperature and the surface is cut to obtain a regular microporous foamed ceramic product.

[0065] The porosity of the foamed ceramic product is 92.3%, the average pore diameter is 0.99 mm, the closed porosity is 98.1%, the compressive strength is 1.95 MPa, and the thermal conductivity is 0.064 W / (m·k).

[0066] Example 5 (1) Remove impurities from cordierite refractory brick waste, corundum refractory waste, silicon carbide plate waste, and copper tailings, dry, crush, grind into micro powder, and then sieve into fine powder for standby use. After sieving, all the cordierite refractory brick waste powder and corundum refractory waste powder pass through a 10μm square hole sieve, and the particles below 1μm are sieved out; all the silicon carbide plate waste powder passes through a 10μm square hole sieve; and all the copper tailings powder passes through a 45μm square hole sieve.

[0067] (2) The obtained cordierite refractory brick waste powder and corundum refractory material waste powder are placed in a high-temperature furnace respectively, wherein the cordierite refractory brick waste powder is heated to 700°C at 6°C / min, kept at this temperature for 60 min, then cooled to 400°C at -2°C / min, kept at this temperature for 120 min, and finally cooled to room temperature with the furnace for use; the corundum refractory material waste powder is heated to 900°C at 10°C / min, kept at this temperature for 60 min, then cooled to 600°C at -2°C / min, kept at this temperature for 30 min, and finally cooled to room temperature with the furnace for use.

[0068] (3) According to the mass proportions, 3 parts of cordierite refractory brick waste powder, 3 parts of corundum refractory material waste powder, 0.2 parts of silicon carbide plate waste powder, 40 parts of copper tailings powder, and 0.1 parts of triethanolamine were placed in a forced mixer and dry mixed at a speed of 50 r / min for 300 min to form a blank.

[0069] (4) The blanks are loosely piled in a refractory sagger, placed in a high-temperature furnace, heated to 1240°C, and kept warm for 60 minutes to sinter and foam.

[0070] (5) The foamed body is cooled to room temperature and the surface is cut to obtain a regular microporous foamed ceramic product.

[0071] The porosity of the foamed ceramic product is 90.6%, the average pore diameter is 0.99 mm, the closed porosity is 98.9%, the compressive strength is 4.05 MPa, and the thermal conductivity is 0.083 W / (m·k).

[0072] Comparative Example 1 Cordierite refractory brick waste, corundum refractory material waste, silicon carbide plate waste and fly ash are used as raw materials.

[0073] (1) Remove impurities from cordierite refractory brick waste, corundum refractory waste, silicon carbide plate waste, and fly ash, dry, crush, grind into micro powder, and then sieve to make fine powder for use. After sieving, all the cordierite refractory brick waste powder and corundum refractory waste powder pass through a 10μm square hole sieve, and the particles below 1μm are sieved out; all the silicon carbide plate waste powder passes through a 10μm square hole sieve; and all the fly ash powder passes through a 45μm square hole sieve.

[0074] (2) The obtained cordierite refractory brick waste powder and corundum refractory material waste powder were placed in a high-temperature furnace respectively. The passivation treatment process parameters of the two wastes were the same as those in Example 5.

[0075] (3) According to the mass proportions, 3 parts of cordierite refractory brick waste powder, 3 parts of corundum refractory material waste powder, 0.2 parts of silicon carbide plate waste powder, 40 parts of fly ash, and 0.1 parts of triethanolamine were placed in a forced mixer and dry mixed at a speed of 50 r / min for 300 min to form a blank.

[0076] (4) The blanks are loosely piled in a refractory sagger, placed in a high-temperature furnace, heated to 1240°C, and kept at this temperature for 60 minutes to form foam.

[0077] (5) After firing, the green body is cooled to room temperature to obtain a sintered ceramic product.

[0078] The porosity of the sintered ceramic product is 15.2%, with no macroscopic pores, a compressive strength of 19.05 MPa, and a thermal conductivity of 0.819 W / (m·k).

[0079] By comparing Example 5 and Comparative Example 1, it can be seen that if fly ash is used as the raw material instead of feldspar solid waste material powder as the main raw material, since sufficient high-temperature melt cannot be generated in the green body under high temperature, even if silicon carbide waste refractory material is used as the foaming agent, low-density porous foamed ceramic products cannot be made.

[0080] Comparative Example 2 Cordierite refractory brick waste, silicon carbide plate waste and feldspar tailings are used as the main raw materials.

[0081] (1) Remove impurities from cordierite refractory brick waste, silicon carbide plate waste, and feldspar tailings, dry, crush, grind into micro powder, and then sieve into fine powder for standby use. After sieving, all the cordierite refractory brick waste powder passes through a 10μm square hole sieve, and particles below 1μm are sieved out; all the silicon carbide plate waste powder passes through a 10μm square hole sieve; and all the feldspar tailings powder passes through a 45μm square hole sieve.

[0082] (2) The obtained cordierite refractory brick waste powder is directly used as raw material without high-temperature passivation pretreatment.

[0083] (3) According to the weight ratio, 6 parts of cordierite refractory brick waste powder, 0.1 parts of silicon carbide plate waste powder, 35 parts of feldspar tailings powder, and 0.1 parts of triethanolamine were placed in a forced mixer and dry mixed at a speed of 120 r / min for 180 min to form a blank.

[0084] (4) The blanks are loosely piled in a refractory sagger, placed in a high-temperature furnace, heated to 1220°C, and kept warm for 60 minutes to sinter and foam.

[0085] (5) The foamed body is cooled to room temperature and the surface is cut to obtain a regular microporous foamed ceramic product.

[0086] The porosity of the foamed ceramic product is 91.1%, the average pore diameter is 1.52 mm, the closed porosity is 95.5%, the compressive strength is 1.88 MPa, and the thermal conductivity is 0.072 W / (m·k).

[0087] By comparing Example 4 and Comparative Example 2, it can be seen that if the cordierite refractory brick waste powder obtained by grinding is directly used as a raw material without passivation treatment, it will partially participate in the reaction of the high-temperature melt at high temperature and be consumed, which will eventually lead to a decrease in the foam stabilizing effect, an increase in the bubble pore size, an increase in the open porosity, and damage to the overall strength of the material.

[0088] Comparative Example 3 Cordierite refractory brick waste, silicon carbide plate waste, and feldspar tailings are used as the main raw materials, and the pretreatment of the raw materials is the same as that in Example 4. The obtained cordierite refractory brick waste powder is placed in a high-temperature furnace, heated to 200°C at 6°C / min, kept warm for 100 minutes, and then cooled to room temperature with the furnace for standby use.

[0089] (3) According to the weight ratio, 6 parts of cordierite refractory brick waste powder, 0.1 parts of silicon carbide plate waste powder, 35 parts of feldspar tailings powder, and 0.1 parts of triethanolamine were placed in a forced mixer and dry mixed at a speed of 120 r / min for 180 min to form a blank.

[0090] (4) The blanks are loosely piled in a refractory sagger, placed in a high-temperature furnace, heated to 1220°C, and kept warm for 60 minutes to sinter and foam.

[0091] (5) The foamed body is cooled to room temperature and the surface is cut to obtain a regular microporous foamed ceramic product.

[0092] The porosity of the foamed ceramic product is 91.8%, the average pore diameter is 1.60 mm, the closed porosity is 94.5%, the compressive strength is 1.56 MPa, and the thermal conductivity is 0.071 W / (m·k).

[0093] By comparing Example 4 and Comparative Example 3, it can be seen that although the cordierite refractory brick waste powder obtained by grinding has undergone passivation treatment, the treatment temperature is low and the surface passivation of the cordierite grains cannot be achieved. It will still partially participate in the reaction of the high-temperature melt at high temperature and be consumed, which ultimately leads to a decrease in the foam stabilizing effect, an increase in the bubble pore size, an increase in the open porosity, and damage to the overall strength of the material.

[0094] It can be seen that the present invention has the following improvements: (1) The raw materials used are aluminum-silica industrial solid waste and waste refractory materials. The main raw materials are solid waste, which not only contributes to the green development of foamed ceramics, but also contributes to environmental protection and the sustainable development of solid waste enterprises.

[0095] (2) Alumina-silica waste refractory materials are used as raw materials, which are prepared into microparticles and incorporated into foamed ceramics. The high melting point grains can be stably present in the molten green body, increasing the melt viscosity and improving the liquid film strength, thereby realizing the preparation of low-density microporous foamed ceramics.

[0096] (3) Using carbon waste refractory materials as foaming agents saves the production cost of foamed ceramics and enables concentrated foaming at high temperature to form small and uniform closed pores.

[0097] (4) There are few types of raw materials, the production process is simple, and dry powder making is adopted, which has low energy consumption. The average pore size of the foamed ceramics produced is less than 1 mm, the porosity is adjustable, and the mechanical properties are excellent. The product cost and performance are more competitive than similar products.

[0098] In the description of this specification, the description with reference to the terms "one embodiment", "certain embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0099] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A low-density microporous foamed ceramic based on waste refractory materials, characterized in that: Calculated by weight, the composition of the blank includes 0.1 to 1 part of carbonaceous waste refractory material, 20 to 40 parts of feldspar solid waste material, 0.1 to 0.2 parts of dispersant and 1 to 6 parts of passivated aluminum silicon waste refractory material.

2. The low-density microporous foamed ceramic based on waste refractory materials according to claim 1, characterized in that: The porosity is 88%~95%, the average pore size is ≤1mm, the closed porosity is ≥96%, the compressive strength is 0.2 MPa~6MPa, and the thermal conductivity is 0.05 W / (m·k)~0.092W / (m·k).

3. The low-density microporous foamed ceramic based on waste refractory materials according to claim 1, characterized in that: The aluminosilicate waste refractory material includes any one of a corundum refractory material, a cordierite refractory material, a spinel refractory material, and an olivine refractory material.

4. The low-density microporous foamed ceramic based on waste refractory materials according to claim 1, characterized in that: The carbonaceous waste refractory material comes from at least one of carbon bricks, graphite bricks, and silicon carbide carbon products, and the refractory temperature is ≥1300°C.

5. The low-density microporous foamed ceramic based on waste refractory materials according to claim 1, characterized in that: The feldspar solid waste material includes at least one of feldspar tailings, copper tailings, lithium tailings, and gold tailings, wherein the content of feldspar minerals is ≥40%, and the chemical composition satisfies: 15%≤Al2O3≤25%, 50%≤SiO2≤80%, Na2O+K2O≥5%, and 2%≤CaO+MgO≤10%.

6. The low-density microporous foamed ceramic based on waste refractory materials according to claim 1, characterized in that: The particle size of the aluminosilicate waste refractory material ranges from 1 μm to 10 μm, the particle size of the carbonaceous waste refractory material is ≤10 μm, and the particle size of the feldspar solid waste is ≤45 μm.

7. The low-density microporous foamed ceramic based on waste refractory materials according to claim 1, characterized in that: The dispersant includes at least one of triethanolamine, cyclohexane acid soap, polysiloxane, tricarboxylic acid ethylamine, sodium polyacrylate, and sodium hexametaphosphate.

8. A method for producing low-density microporous foamed ceramics based on waste refractory materials, characterized in that: The steps include: Aluminosilicate waste refractory materials, carbonaceous waste refractory materials and feldspar solid waste materials are respectively subjected to impurity removal, drying, crushing and grinding to form micro powders, and then sieved to obtain fine powders; placing the fine powder obtained from the aluminum-silicon waste refractory material in a high-temperature furnace for passivation treatment and then cooling; 1 to 6 parts by mass of the passivated fine powder made from the aluminum-silicon waste refractory material, 0.1 to 1 part of the fine powder made from the carbonaceous waste refractory material, 20 to 40 parts of the fine powder made from the feldspar solid waste material, and 0.1 to 0.2 parts of the dispersant are placed in a forced mixer and dry mixed for 180 minutes to 480 minutes to form a blank; The blank is piled in a refractory sagger or pressed into shape by a press, and then placed in a high-temperature furnace, heated to 1150° C. to 1250° C., kept warm for 30 min to 90 min, fired and foamed, to obtain a low-density microporous foamed ceramic based on waste refractory materials.

9. The method for producing low-density microporous foamed ceramics based on waste refractory materials according to claim 8, characterized in that: The passivation treatment process is: heating to 500°C~900°C at 5°C / min~12°C / min, keeping warm for 10min~60min, then cooling to 400°C~800°C at -2°C / min, keeping warm for 30min~180min, and finally cooling to room temperature with the furnace.

10. The method for producing low-density microporous foamed ceramics based on waste refractory materials according to claim 8, characterized in that: The forced mixer is a fast powder mixer with eccentric stirring blades, and the stirring speed is 50 r / min~200 r / min.

Citation Information

Patent Citations

  • Preparation process of partition board made of ceramics factory waste

    CN102898080A

  • Method for recycling mixed material dreg of overhauling groove slag of electrolytic cell

    CN102989744A

  • Production method of corundum-mullite lightweight brick

    CN109133880A

  • Method for preparing gradient density microcrystal foaming ceramic by utilizing industrial solid waste

    CN117776763A

  • Lightweight cellular ceramics, its production, lightweight cellular tile and tiled board with the tile

    JP2000290083A